Confined Thermolysis for Oriented N‐Doped Carbon Supported Pd toward Stable Catalytic and Energy Storage Applications. Issue 22 (30th July 2020) - Huang, Ke‐Xin; Hua, Junhui; Chang, Gang‐Gang; Li, Zhaohuai; Tian, Ge; Chen, Min‐Jie; Li, Jia‐Xin; Ke, Shan‐Chao; Yang, Xiao‐Yu; Chen, Banglin
Abstract: Carbon‐based nanomaterials have been widely utilized in catalysis and energy‐related fields due to their fascinating properties. However, the controllable synthesis of porous carbon with refined morphology is still a formidable challenge due to inevitable aggregation/fusion of resulted carbon particles during the high‐temperature synthetic process. Herein, a hierarchically oriented carbon‐structured (fiber‐like) composite is fabricated by simultaneously taking advantage of a confined pyrolysis strategy and disparate bond environments within metal–organic frameworks (MOFs). In the resultant composite, the oriented carbon provides a fast mass (molecule/ion/electron) transfer efficiency; the doping‐N atoms can anchor or act as active sites; the mesoporous SiO2 (mSiO2 ) shell not only effectively prevents the derived carbon or active metal nanoparticles (NPs) from aggregation or leaching, but also acts as a "polysulfide reservoir" in the Li–S batteries to suppress the "shuttle" effect. Benefiting from these advantages, the synthesized composite Pd@NDHPC@mSiO2 (NDHPC means N‐doped hierarchically porous carbon) exhibits extremely high catalytic activity and stability toward the one‐pot Knoevenagel condensation–hydrogenation reaction. Furthermore, the oriented NDHPC@mSiO2 manifests a boosted capacity and cycling stability in Li–S batteries compared to the counterpart that directly pyrolyzes without silica protection. This report provides an effective strategy of fabricating hierarchically oriented carbon composites for catalysis and energy storage applications. Abstract : An N‐doped oriented carbon‐structured (fiber‐like) composite with hierarchical pore and ultrafine Pd nanoclusters is fabricated by simultaneously taking advantage of the confined pyrolysis strategy and disparate bond environments within metal–organic frameworks (MOFs). The synthesized composite Pd@NDHPC@mSiO2 manifests extremely high catalytic activity toward tandem catalysis and much boosted cycling stability in Li–S batteries.